Versatile heteroleptic bis-terdentate Cr(iii) chromophores displaying room temperature millisecond excited state lifetimes. Issue 94 (8th November 2018) - Jiménez, Juan-Ramón; Doistau, Benjamin; Besnard, Céline; Piguet, Claude
Abstract : Cr–Br bonds can be specifically labilized for producing phosphorescent and tuneable heteroleptic bis-terdentate Cr(iii ) long-lived sensitizers. Abstract : Substitution of Ru(ii )-based chromophores with cheaper Cr(iii )-based complexes in optically active metallo-supramolecular architectures is limited by the lack of synthetic strategies leading to heteroleptic Cr(iii )-polypyridyl complexes with long excited-state lifetimes. Herein, we report on a versatile method yielding heteroleptic bis(terdentate) Cr(iii ) complexes with room temperature millisecond range excited-state lifetimes, tuneable electronic and photophysical properties and easy anchoring possibilities.